Sosialisasi Sistem Informasi Penelitian dan Pengabdian LPPM UWHS - Rozaq Isnaini Nugraha; Arif Fitra Setyawan (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The management of research and community service data in higher education institutions is crucial for achieving Key Performance Indicators (IKU) and supporting the Merdeka Belajar Kampus Merdeka (MBKM) policy. At Widya Husada University Semarang (UWHS), data recording and reporting processes for research and community service still face various challenges, including low efficiency, lack of accuracy, and limited system integration. To address these issues, a community service program was conducted through the socialization and implementation of a web-based Internal Research and Community Service Information System (BIMA) under the UWHS Research and Community Service Institute (LPPM). The method employed consists of five stages: socialization, training, technology implementation, mentoring and evaluation, and program sustainability. The results indicate that the developed system successfully enhances reporting efficiency, process transparency, and digital literacy among lecturers. Moreover, it improves lecturers’ ability to independently manage their research and community service proposals, especially in preparing for national research and service grant opportunities.